(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reciprocity relationships are a necessity in human life. This study aims to describe the various factors that determine the formation of balanced reciprocity in the relationship between land owners and farm laborers. The research’s location was determined intentionally in the rural areas of Purbalingga Regency and Banyumas Regency, Central Java Province, Indonesia. This study used a qualitative method with a semi-grounded phenomenological research design. The results showed that a balanced reciprocity relationship was determined by a variety of principal and smoothing factors. The identification results showed that the main determinants include opportunity, benefit, mutual trust, closeness of social relations, motives for reciprocal exchange, openness in communication, willingness to give transactions to accept and return. The array of determinants of smoothing factors is routine contact and communication, empathy, tolerance, length of relationship, regularity of social interactions, network of cooperation, solidarity, transaction ability, mutual control and evaluation. The existence and strength of these two types of determining factors have an important function in the formation of balanced reciprocity among agricultural land owners and farm laborers. Willingness, self-awareness and opportunity are very important to develop to form balanced reciprocity.